2013
DOI: 10.1179/2045772312y.0000000068
|View full text |Cite
|
Sign up to set email alerts
|

Criterion validity and accuracy of global positioning satellite and data logging devices for wheelchair tennis court movement

Abstract: Sampling frequencies of 1 Hz are too low to accurately measure distance and speed during wheelchair tennis. GPS units with a higher sampling rate should be advocated in further studies. Modifications to existing DL devices may be required to increase measurement precision. Further research into the validity of movement devices during match play will further inform the demands and movement patterns associated with wheelchair tennis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 29 publications
3
61
2
4
Order By: Relevance
“…The specifications of each device are shown in Appendix 2. Of the 29 articles selected, 6 studies evaluated commercially available monitors with default algorithms for quantifying PA in MWUs [24][25][26][27][28][29] (Appendix 3), 15 evaluated commercially available monitors with custom algorithms [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] (Appendix 4), and 10 evaluated custom-made devices and algorithms [43][44][45][46][47][48][49][50][51][52] (Appendix 5). These activity monitors could be categorized into three types: accelerometer-based, multisensor-based, and others (gyroscope-or HR-based).…”
Section: Literature Searchesmentioning
confidence: 99%
See 3 more Smart Citations
“…The specifications of each device are shown in Appendix 2. Of the 29 articles selected, 6 studies evaluated commercially available monitors with default algorithms for quantifying PA in MWUs [24][25][26][27][28][29] (Appendix 3), 15 evaluated commercially available monitors with custom algorithms [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] (Appendix 4), and 10 evaluated custom-made devices and algorithms [43][44][45][46][47][48][49][50][51][52] (Appendix 5). These activity monitors could be categorized into three types: accelerometer-based, multisensor-based, and others (gyroscope-or HR-based).…”
Section: Literature Searchesmentioning
confidence: 99%
“…Among the 29 articles, 14 investigated accelerometer-based monitors (1 uniaxial [38] and 13 triaxial [26,[32][33][39][40][41][42][46][47][48][49][50][51]), 9 evaluated multisensor-based devices [24][25][28][29]31,[34][35][36][37], 1 evaluated a gyroscope-based monitor [44], and 5 evaluated combinations of any 2 of the 3 types [27,30,43,45]. Among all articles, 19 included only MWUs with spinal cord injuries (SCIs) [24,[26][27][28][29]31,[33][34][35][36][37][40][41][43][44]46,[50][51][52]; 7 included MWUs with a mix of diagnoses, including SCI, amputation, congenital bone disorder, complex regional pain syndrome, CharcotMarie-Tooth disease, demyelinating disease, dystonia, fib...…”
Section: Literature Searchesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, laboratory tests have shown that this method could underestimate speeds when a wheelchair travels at speeds greater than 2.5 m/s (5.6 miles per hour). 15 Our observation of the problem with the existing devices at higher speeds has led us to design and develop a gyroscope based G-WRM that can capture a range of speeds from wheelchair propulsion to handcycling.…”
Section: Methods Developmentmentioning
confidence: 99%